Synthesis and Antioxidant Test of 1,5-bis(3’-etoksi-4’- hidroksifenil)-1,4-pentadien-3-on (EHP) Compound - MUMPUNI, ESTI; RUSNAWAN, ENJANG; SULASTRI, EVI; PERMATASARI, INDRIANA (JURNAL ILMU KEFARMASIAN INDONESIA; Vol 8 No 2 (2010): JIFI, 2010)
Synthesis of 1,5-bis(3’-etoxy-4’-hydroxyphenyI)-1,4-pentadiene-3-on (EHP) by aldol condensation method from ethyl Vanilin and acetone, using hydrochloride acid as a catalyst, has been conducted. Identification of the EHP compound was done through interpretation of UV-Vis, FT-IR, GC-MS and NMR data, The antioxidant activity of EHP (IC 50 8.66 µg/mL) is higher than curcumin (IC 50 11.44 µg/mL) as demonstrated by the DPPH method.